Health-related quality of life of the elderly with cancer in adjuvant treatment - Toneti, Bruna Francielle; Paula, Juliana Maria de; Nicolussi, Adriana Cristina; Sawada, Namie Okino (Rev Rene, 2014)
This study aimed at identifying changes in the quality of life of older people with cancer and characterizing the socio-demographic, clinical and therapeutic data, associating them with domains of health-related quality of life. This is a cross-sectional study, conducted in a private clinic in Ribeirão Preto, Brazil, from August 2012 to July 2013. It was carried out with 21 elderly patients with cancer and in adjuvant treatment. The instrument Quality of Life Questionnaire Core-30 (QLQ-C30) and a socio-demographic, clinical and therapeutic instrument were used to collect data which were then analyzed by the Statistical Package for Social Science software. The results showed that the general quality of life was satisfactory (average = 69.04), the main affected domains were emotional function, social function, cognitive function, financial difficulties, fatigue, nausea and vomiting, dyspnea, and insomnia. The disease and the treatment interfere with the lives of the elderly and affect their health-related quality of life.